What does it mean to be Lean in SoSE environment?. Issue 1 (13th September 2016) - Tregubov, Alexey; Lane, Jo Ann
Abstract: While Lean practices are common across many fields and domains today, adaptation of Lean in system engineering began not so long ago. Value‐driven processes with minimum waste are especially important in system of systems environments. In this paper, we discuss how system of systems engineering (SoSE) processes differ from single system development processes, and how Lean practices are often employed in SoSE. Finally, we explored the original Lean enablers for system engineering, developed by the INCOSE Lean System Engineering Working Group, and discussed how these enablers can be applied to SoSE.